2021
DOI: 10.1089/sur.2020.426
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections after Laparoscopic Bariatric Surgery: Is Routine Antibiotic Prophylaxis Required?

Abstract: Background: It is a challenging question, especially in bariatric surgery (BS), whether antibiotic prophylaxis is necessary in all cases; considering the serious consequences of surgical site infection (SSI) on the one hand and irrational use of antibiotics on the other. The aim of this study was to determine the need/rationale for antibiotic prophylaxis in patients undergoing laparoscopic bariatric surgery, especially low-risk patients. Methods: This retrospective analysis involved 313 morbidly obese patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Antibiotics is another factor that has been shown to alter gut microbiota. Perioperative antibiotic prophylaxis is been questioned to be necessary for reducing surgical site infections in patients undergoing laparoscopic bariatric surgery [111]. Indeed, Jacobson et al suggested a role for antibiotic-induced dysbiosis in weight loss after SG.…”
Section: Gut Microbiota Manipulation Complementary To Bariatric Surgerymentioning
confidence: 99%
“…Antibiotics is another factor that has been shown to alter gut microbiota. Perioperative antibiotic prophylaxis is been questioned to be necessary for reducing surgical site infections in patients undergoing laparoscopic bariatric surgery [111]. Indeed, Jacobson et al suggested a role for antibiotic-induced dysbiosis in weight loss after SG.…”
Section: Gut Microbiota Manipulation Complementary To Bariatric Surgerymentioning
confidence: 99%
“…For example, in elective laparoscopic cholecystectomy without acute inflammation, surgical antibiotic prophylaxis has demonstrated minimal or no reduction in SSIs for low-risk patients . Similarly, no benefit from routine antibiotic prophylaxis has been shown for laparoscopic sleeve gastrectomy, laparoscopic roux-en-Y gastric bypass, endoscopic polypectomy, and open or transoral thryroidectomy or parathyroidectomy . For outpatient procedures such as ophthalmologic, dermatologic, fertility, or dental procedures, antibiotic use remains common, but has been shown to be unnecessary in many cases …”
Section: Discussion and Observationsmentioning
confidence: 99%